2017
DOI: 10.3329/bjms.v16i2.31941
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of USG-guided FNAC with conventional FNAC in the preoperative assessment of thyroid lesions: A particular reference to cyto-histologically discordant cases.

Abstract: Abstract:Aims & Objectives: To assess the relative usefulness of ultrasound (USG) guided fine needle aspiration cytology (FNAC) in diagnosis of thyroid lesions over conventional FNAC (C-FNAC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Different workers reported that failure to aspirate from proper site was the major cause of misdiagnosis during cytological evaluation. Also, high inadequacy rate, (ranging from 6.4 to 32.4%) as found in various studies; is another major limitation of conventional FNAC [2] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different workers reported that failure to aspirate from proper site was the major cause of misdiagnosis during cytological evaluation. Also, high inadequacy rate, (ranging from 6.4 to 32.4%) as found in various studies; is another major limitation of conventional FNAC [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound guided FNAC (USG-FNAC) was first introduced by Rizatto et al in 1973. Since then, several studies have reported that USG-FNAC reduces the inadequacy rate of conventional FNAC [2] . USG-guided FNAC has the major advantage of real time monitoring which help in accurate localisation of needle tip during aspiration [2] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] Ultrasonography has been widely used as a noninvasive diagnostic method in assessing thyroid and ovarian lesions. 9,10 Since 1970, US has been used as an intraoperative diagnostic tool. 11,12 The restriction of subcortical brain tumors, in any case, has constantly presented issues to neurosurgeons.…”
Section: Introductionmentioning
confidence: 99%